2022
DOI: 10.1111/jcpt.13672
|View full text |Cite
|
Sign up to set email alerts
|

The role of the genetic variant FECH rs11660001 in the occurrence of anti‐tuberculosis drug‐induced liver injury

Abstract: What is known and objective The pathogenic mechanism of anti‐tuberculosis drug‐induced liver injury (AT‐DILI) is still largely unknown. Recent studies have indicated that rifampicin and isoniazid cotreatment causes the accumulation of endogenous protoporphyrin IX in the liver through the haem biosynthesis pathway. Alanine synthase 1 (ALAS1) and ferrochelatase (FECH) are the rate‐limiting enzymes in the production of haem. The present study aimed to investigate the genetic contribution of the ALAS1 and FECH gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Alanine synthase 1 and ferrochelatase are the key enzymes regulating heme production. Zhang et al [ 114 ] identified that the polymorphism rs11660001 in ferrochelatase in women is related to the development of ATDILI. Anti-TB drugs generally target constantly replicating bacteria, so a state of latency is a delay in the fight against TB.…”
Section: Limitations Of Conventional Therapies In Tb Treatmentmentioning
confidence: 99%
“…Alanine synthase 1 and ferrochelatase are the key enzymes regulating heme production. Zhang et al [ 114 ] identified that the polymorphism rs11660001 in ferrochelatase in women is related to the development of ATDILI. Anti-TB drugs generally target constantly replicating bacteria, so a state of latency is a delay in the fight against TB.…”
Section: Limitations Of Conventional Therapies In Tb Treatmentmentioning
confidence: 99%